2019
DOI: 10.3389/fpls.2019.00552
|View full text |Cite
|
Sign up to set email alerts
|

Application of Remote Sensing for Phenotyping Tar Spot Complex Resistance in Maize

Abstract: Tar spot complex (TSC), caused by at least two fungal pathogens, Phyllachora maydis and Monographella maydis , is one of the major foliar diseases of maize in Central and South America. P. maydis was also detected in the United States of America in 2015 and since then the pathogen has spread in the maize growing regions of the country. Although remote sensing (RS) techniques are increasingly being used for plant phenotyping, they have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 51 publications
0
32
0
1
Order By: Relevance
“…Limited options are currently available for disease or pest damage detection, spatial distribution, and evaluation. Canopy reflectance in visual and near-infrared wavebands has been used at CIMMYT-Mexico for tar spot complex phenotyping in maize (Loladze et al 2019 ).…”
Section: Increasing Genetic Gain In the Stress-prone Tropical Environmentioning
confidence: 99%
“…Limited options are currently available for disease or pest damage detection, spatial distribution, and evaluation. Canopy reflectance in visual and near-infrared wavebands has been used at CIMMYT-Mexico for tar spot complex phenotyping in maize (Loladze et al 2019 ).…”
Section: Increasing Genetic Gain In the Stress-prone Tropical Environmentioning
confidence: 99%
“…Tenkorang and Lowenberg-Doboer [102] reported that in agriculture, remote sensing has the potential to improve average on-farm profit by about $31.74/ha at standardized budget assumptions. The localization of maize experimental site at CIMMYT Mexico on fungicide and non-fungicide treatments was reported using remote sensing techniques (Figure 2a) [103], crop acreage estimate at the peak of crop growth during growing season using SPOT-5 satellite (Figure 2b), and monthly SPOT NDVI crop phenology behavior in a rainfed area of Punjab (Figure 2c) [104].…”
Section: Remote Sensingmentioning
confidence: 99%
“…High-throughput imaging phenotyping techniques are increasingly being used in crop improvement (Araus and Cairns, 2014;Xu et al, 2019;Loladze et al, 2019;Juliana et al, 2019). The most successful study was the application of multispectral camera by Xu et al (2019) to phenotype cotton accessions for canopy cover, as illustrated in Figure 3.…”
Section: Phenotyping For Abiotic Stress Tolerance and Resource Use-efmentioning
confidence: 99%
“…The application was not only efficient in terms of reduced time, but also a strong correlation (R 2 = > 0.92) was found between calculated and measured maximum plant heights and a moderate association (R 2 = 0.32-0.57) between normalized vegetation index and canopy cover. Similarly, Loladze et al (2019) also applied hyperspectral and infrared thermal cameras to phenotype grain yield in maize (Zea mays L.) with different levels of disease infection. The study not only showed strong relationships between grain yield, vegetation index, and canopy temperature under disease pressure ( Table 5), but also demonstrated that imaging techniques could help reduce the time and cost required for the development of improved maize germplasm.…”
Section: Phenotyping For Abiotic Stress Tolerance and Resource Use-efmentioning
confidence: 99%